Modelling of structures and properties of polymer-bitumen binding methods of experiment planning - V. D. Galdina; M. S. Chernogorodova (Вестник СибАДИ)
With application of a method of mathematical planning of experiment mathematical models of technological and operational properties polimerno-bitumen knitting on the basis of viscous road bitumen, polymer of type styrene-butadien-styrene and the softener are received, allowing to optimise structures and to predict properties of the knitting. Experiment planning considerably reduces procedure of selection of structures of polimerno-bitumen physicomechanical properties knitting with a demanded complex